Pengolahan Limbah Domestik Menggunakan Hibrid Biofilter dan Sistem Hidroponik NFT dalam Budidaya Selada (Lactuca Sativa L) - Kisworo; Ricky Albertus; Haryati Sutanto Bawole (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2020)
It cannot be denied that the domestic wastewater is a problem for the environment. Untreated wastewater can cause environmental damaging and bring a negative impact on the organism’s health especially humans. Treating the wastewater before disposing, can reduce its impact. Biofilter is one of the wastewater treatment system that utilizing microorganisms on the filtration media to reduce the organic loading. Not all organic loads are processed in the biofilter, then the other processed is needed to maximize the result as an unified system. This study is was about a hybrid biofilter and hydroponic system in treating domestic wastewater. The hydroponic system used is NFT (Nutrient Film Technique). The cultivated plants are Lettuce (Lactuca sativa L). Lettuce can absorb nutrients such as nitrates and phosphates from the treatment of liquid waste. The parameter that measured such as Ammoniac, Nitrate, Phosphate, TDS, BOD, DO, temperature, and pH with the retention time or Hydraulic Retention Time (HRT) for 5 days. The efficiency of decreasing the parameters of TDS, BOD, DO, ammonia, and phosphate in hybrid hydroponic system biofilter reactors were 31.5%, 51.6%, 99.7%, and 50.1%, respectively.